Personnel training for common facility management issues in Thermal-Energy-Storage chiller plant using a serious 3D game - Sanzana, Mirza Rayana; Abdulrazic, Mostafa Osama Mostafa; Wong, Jing Ying; Yip, Chun-Chieh (Sage, 2023)
Background. This study introduces an innovative personnel training method for facility management and maintenance of Thermal-Energy-Storage (TES) chiller plants using a serious 3D game. Training games can improve the decision making of personnel where they can learn to deal with management of TES chiller plants in the context of this study in an active learning approach.